2010
DOI: 10.1016/j.jaac.2010.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Genome-Wide Association Studies of Attention-Deficit/Hyperactivity Disorder

Abstract: Objective Although twin and family studies have shown Attention Deficit/Hyperactivity Disorder (ADHD) to be highly heritable, genetic variants influencing the trait at a genome-wide significant level have yet to be identified. As prior genome-wide association scans (GWAS) have not yielded significant results, we conducted a meta-analysis of existing studies to boost statistical power. Method We used data from four projects: a) the Children’s Hospital of Philadelphia (CHOP), b) phase I of the International Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
393
4
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 431 publications
(412 citation statements)
references
References 35 publications
6
393
4
9
Order By: Relevance
“…A number of candidate genes have been associated, but altogether explain only a small part of the heritability 3 , and so far, genome-wide association studies (GWASs) have not yielded genome-wide significant findings 4 . Difficulty in discovering genetic risk variants has been attributed to the fact that ADHD is clinically heterogeneous 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of candidate genes have been associated, but altogether explain only a small part of the heritability 3 , and so far, genome-wide association studies (GWASs) have not yielded genome-wide significant findings 4 . Difficulty in discovering genetic risk variants has been attributed to the fact that ADHD is clinically heterogeneous 5 .…”
Section: Introductionmentioning
confidence: 99%
“…As genome-wide genetic analyses aimed at identifying common risk variants, mainly focused on investigating Single Nucleotide Polymorphisims (SNPs) 10-12 association, extremely large samples are needed to achieve genome-wide significance 4,13 and sample sizes in ADHD research are still small compared to other disorders 13 . A recent study performing cross-disorder GWAS using data from the Psychiatric Genomics Consortium of cases and controls for schizophrenia, bipolar disorder, major depressive disorder, autism spectrum disorders and ADHD, showed a significant polygenic component for ADHD, suggesting that searching for a combination of genetic variants might be fruitful 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Two of these articles report results from genetic studies (23,31), and one reports a computational simulation study (32) The 7R was associated with ADHD in a meta-analysis of candidate gene studies (33), but the odds ratio was low (only 1.3). Furthermore, DRD4 has not yet been implicated by genome-wide association studies (34) and current thinking is that ADHD susceptibility is influenced by many common and rare variants (9). Similarly, the study by Williams et al is based on the assumption that individuals with ADHD are unpredictable (32), which may be true in some, but certainly not in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies are inconclusive, but candidate genes studies have found evidence for the association of various genes with elevated risk for ADHD. 48,49 This may suggest that each genetic marker accounts for only a small proportion of heritability, indicating that ADHD arises from a complex interaction of genetic susceptibility and environmental conditions. 50,51 Numerous possibilities of gene combinations added to countless possible interactions with environmental conditions generate pronounced heterogeneity from the genetic point of view.…”
Section: Adhd As a Heterogeneous Disordermentioning
confidence: 99%